2020
DOI: 10.1186/s12870-020-02566-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Contribution of anthocyanin pathways to fruit flesh coloration in pitayas

Abstract: Background: Color formation in Hylocereus spp. (pitayas) has been ascribed to the accumulation of betalains. However, several studies have reported the presence of anthocyanins in pitaya fruit and their potential role in color formation has not yet been explored. In this study, we profiled metabolome and transcriptome in fruit of three cultivars with contrasting flesh colors (red, pink and white) to investigate their nutritional quality and the mechanism of color formation involving anthocyanins. Results: Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 67 publications
1
25
4
1
Order By: Relevance
“…Anthocyanins also contribute to fruit color, such as in Hylocereus spp. (Fan et al, 2020) and Morus atropurpurea (Huang et al, 2020). Moreover, anthocyanin has various other functions in plants, including in the protection against abiotic stresses, resistance to pathogens, tolerance to environmental stresses, and pollinator attraction (Schaefer et al, 2004;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins also contribute to fruit color, such as in Hylocereus spp. (Fan et al, 2020) and Morus atropurpurea (Huang et al, 2020). Moreover, anthocyanin has various other functions in plants, including in the protection against abiotic stresses, resistance to pathogens, tolerance to environmental stresses, and pollinator attraction (Schaefer et al, 2004;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [ 9 ] did not report the detection of betalains in the fruits of Hylocereus cultivars in their analyses. But as cited by Fan et al [ 9 ], a range of betalain pigments have previously been detected by numerous studies in the same species [ 10 14 ].…”
Section: Main Textmentioning
confidence: 99%
“…With this as context, Fan et al [ 9 ] recently reported anthocyanins within the betalain-pigmented genus Hylocereus (Cactaceae), also commonly called Pitaya. Fan et al [ 9 ] analysed the fruits of three closely related species – a red-fleshed Hylocereus polyrhizus, a white-fleshed Hylocereus undatus , and an intermediate pink-fleshed hybrid ( H. polyrhizus x H. undatus ). Based on the analysis, they reported to correlate the accumulation of anthocyanins with the colour of red and pink fruit pulps, and the expression levels of anthocyanin biosynthesis genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that there may be competition between betalanins and anthocyanin metabolic pathway in pitaya. Anthocyanin contributes to the development of pitaya's color partly (Fan et al, 2020).…”
Section: Disscussionmentioning
confidence: 99%